Responsible and Sustainable Tourism: A Comparison of Community Perceptions - Mathew, Paul V; Thankachan, Sara Sareena (Journal of Tourism Management Research, 2019)
Responsible tourism (RT) has emerged as a significant means of implementing a pro-community, pro-poor, and sustainable program. As the term is relatively new, it is attracting considerable attention worldwide. However, it is often confused with sustainable tourism (ST) due to sharing similar underlying principles. This article thus endeavors to analyze the theoretical basis of both concepts by examining community perceptions in tourist destinations. A structured survey questionnaire was first administered among 387 residents from four tourist destinations in the Indian state of Kerala. Following the data analysis, it was observed that responsible tourism is significantly linked to sustainable tourism. Furthermore, the former fulfills the objectives of the latter in such a way that rather being different from sustainable tourism, it is a limited version of it. Whereas sustainable tourism is more a theoretical concept, responsible tourism is an action component with more practical implications. Consequently, the findings provide insights for academicians and policymakers into defining and implementing both concepts at various levels.